Digestive adaptations to aerial lifestyles - Price, Edwin (2015)
Flying vertebrates (birds and bats) are under selective pressure to reduce the size of the gut and the mass of the digesta it carries. Compared to similar sized non-flying mammals, birds and bats have smaller intestines and shorter retention times. We review evidence that birds and bats have lower spare digestive capacity and partially compensate for smaller intestines with increased paracellular nutrient absorption.